Work engagement in collaborators of gastronomic establishments of Tarma - Paredes Pérez, Marco Antonio (2025)
Objective. Objective To determine the level of work engagement in workers from Tarma chicken shops, Methods: The research was of a basic type, descriptive level and simple, transversal descriptive design, the specific methods were observational, inductive and deductive; the technique was the survey and the instrument was the Uwes Scale of work engagement; the results were processed on a scale from 1 to 4, where 1 was equal to never, 2 almost never, 3 almost always, and 4 always; then ranges were established based on the method of maximum and minimum of scales, recoding the variable in three levels of assessment and interpretation high, medium and low, the sampling was intentional non-probabilistic, the study units were 10 poultry from Tarma and the 80 collaborators of such organizations, Results: The level of engagement in collaborators of establishments of gastronomic consumption of Tarma is medium, as are the dimensions of vigor, dedication and absorption Conclusions: the collaborators are relatively satisfied with their current job, until they find a better opportunity, since they consider that this type of work is temporary in relation to their life projects.